探討授課研究對大學英語兼任教師教學之影響 - 李多耕(To-Ken Lee) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2021)
College instructors of English as a Foreign Language (EFL) in Taiwan typically work alone when planning their teaching activities. In particular, adjunct instructors work isolated during class planning and teaching, and have fewer opportunities for professional development than fulltime instructors. This study attempts to propose a model for collaborative lesson study group for EFL adjunct instructors in a private college in Taiwan and investigates how the practices of these teacher participants can be advanced. Data collection in this study consists of qualitative inquiries, classroom observations and interview transcripts. The results indicate that the execution of a collaborative lesson study group of college adjunct faculties enhance teachers’ collaboration, improve instructional wording, and forge a teachers’ learning community. A collaborative study group for lesson construction helps to build a reciprocal model of learning, where teachers can help each other to identify their instructional weakness or